Method to quantitatively assess electrode migration from medical images: Feasibility and application in patients with straight cochlear implant arrays. (3rd September 2019) - Tanaka Massuda, Eduardo; Demarcy, Thomas; Hoen, Michel; Danieli, Fabiana; Arantes do Amaral, Maria Stella; Gnansia, Dan; Hyppolito, Miguel Angelo
Abstract : Objective: To propose a method for quantitative assessment of the migration of lateral-wall, straight electrode arrays after surgery based on postoperative Cone Beam Computed Tomography (CBCT) images and automated medical image analysis techniques. Methods: A preliminary study is conducted on 19 implanted ears. For each implantation, two CBCT images are objectively analyzed. Electrode arrays are consistently projected into the same coordinate system in order to estimate precisely the migration of each electrode. Spatial configuration changes are characterized with the overall curvature of the electrode array. Results: From the samples analyzed no significant electrode migration, extrusion or electrode curvature changes were found. Mean infinitesimal local migration reveals a tendency where apical electrodes tend to move away from the modiolus and basal electrodes away from the round window. Conclusion: CBCT images demonstrate adequate resolution with limited artifacts to assess the electrode array position in vivo . Automated medical image analysis techniques and consistent coordinate system allow to quantitatively estimate migration and extrusion effect for lateral-wall, straight electrode array.